2015
DOI: 10.1111/pan.12781
|View full text |Cite
|
Sign up to set email alerts
|

Pain outcomes in children who received intrathecal vs intravenous opioids for pain control following major urologic surgery: a retrospective review

Abstract: We observed better postoperative pain control in children who received IT vs IV opioids for the first 16 h with no discernible difference thereafter. The intrathecal group experienced higher incidences of pruritus, constipation, and hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 18 publications
1
12
1
Order By: Relevance
“…The application of medical treatment methods in treating postoperative pain in children who underwent ureteroneocystostomy surgery is limited. The use of opioids in the relief of this pain is limited in children [4]. The use of non-steroidal anti-inflammatory drugs increases the risk in this patient group due to the possibility of potential renal damage.…”
Section: Efficacy Of Ultrasound-guided Transversalis Fascia Plane Block In Pediatric Ureteroneocystostomy Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…The application of medical treatment methods in treating postoperative pain in children who underwent ureteroneocystostomy surgery is limited. The use of opioids in the relief of this pain is limited in children [4]. The use of non-steroidal anti-inflammatory drugs increases the risk in this patient group due to the possibility of potential renal damage.…”
Section: Efficacy Of Ultrasound-guided Transversalis Fascia Plane Block In Pediatric Ureteroneocystostomy Surgerymentioning
confidence: 99%
“…Caudal analgesia is one of these methods and provides adequate postoperative analgesia. However, carries risks such as dural puncture, drug administration to the subarachnoid space, constipation, or hypotension [4]. In addition, it is a limited method because it requires a lateral decubitus position for the procedure and premature closure of the hiatus sacralis in some children.…”
Section: Efficacy Of Ultrasound-guided Transversalis Fascia Plane Block In Pediatric Ureteroneocystostomy Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Pruritus is one of the most common and bothersome side effects of intrathecal morphine in children, with a reported incidence of 30%-60%. [1][2][3] In a retrospective review of intrathecal morphine for urologic surgery in children, a study from our institution found a 40% incidence of pruritus. 2 Clinicians who have witnessed unbearable itching and scratching in their young patients after intrathecal morphine may be reluctant to offer this effective pain control to future patients for fear of these unpleasant sequelae.…”
Section: Introductionmentioning
confidence: 98%